2016
DOI: 10.1177/0022034516661774
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Posttraumatic Stress Disorder Symptomatology in Orofacial Pain

Abstract: To explore the impact of interactions between smoking and symptoms of posttraumatic stress disorder (PTSD) on pain intensity, psychological distress, and pain-related functioning in patients with orofacial pain, a retrospective review was conducted of data obtained during evaluations of 610 new patients with a temporomandibular disorder who also reported a history of a traumatic event. Pain-related outcomes included measures of pain intensity, psychological distress, and pain-related functioning. Main effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…The PTSD population studied consisted of war veterans with an average age of 42 years and with medical PTSD diagnosis. The positive association between PTSD symptoms and variables such as pain intensity, disability, psychological dysfunction, difficulties in coping with pain, interference with daily activities and sleep problems were found in three studies 6,17,18 . Finally, a cohort study reported that PTSD predicted the incidence of painful TMD in healthy populations with a risk ratio of 1.38 19 .…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The PTSD population studied consisted of war veterans with an average age of 42 years and with medical PTSD diagnosis. The positive association between PTSD symptoms and variables such as pain intensity, disability, psychological dysfunction, difficulties in coping with pain, interference with daily activities and sleep problems were found in three studies 6,17,18 . Finally, a cohort study reported that PTSD predicted the incidence of painful TMD in healthy populations with a risk ratio of 1.38 19 .…”
Section: Resultsmentioning
confidence: 92%
“…PTSD development after traumatic events is associated with increased risk of musculoskeletal pain and functional somatic syndromes (FSS) 33,34 . In addition, subjects with both conditions, TMD and PTSD, presented greater pain intensity, psychological dysfunction, interference with daily activities, sleep problems and pain coping difficulties when compared to subjects without PTSD 6,17,18 . These results may be reflective of changes in pain processing found in PTSD subjects.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations